2014
DOI: 10.1038/modpathol.2013.248
|View full text |Cite
|
Sign up to set email alerts
|

ERG expression in intraductal carcinoma of the prostate: comparison with adjacent invasive prostatic adenocarcinoma

Abstract: Intraductal carcinoma of the prostate is a growth pattern of prostatic adenocarcinoma that has not been well characterized from the molecular standpoint. It remains debatable whether intraductal carcinoma of the prostate represents colonization of benign glands by pre-existing conventional prostatic adenocarcinoma, or progression of high-grade prostatic intraepithelial neoplasia. TMPRSS2-ERG is the most common gene fusion in conventional prostatic adenocarcinoma, identified in about 40-70% of cases. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 16 publications
4
18
0
Order By: Relevance
“…They found identical ERG expression in IDC and the adjacent invasive carcinoma similar to our study and concluded that IDC most likely represented colonization of benign glands by adjacent preexisting invasive carcinoma. 21 In our current study, we found that the ERG status of all AIP foci were identical to the ERG status of the nearby invasive carcinoma similar to our previous observations. 8 This contrasted with the ERG status of HGPIN.…”
Section: Discussionsupporting
confidence: 90%
“…They found identical ERG expression in IDC and the adjacent invasive carcinoma similar to our study and concluded that IDC most likely represented colonization of benign glands by adjacent preexisting invasive carcinoma. 21 In our current study, we found that the ERG status of all AIP foci were identical to the ERG status of the nearby invasive carcinoma similar to our previous observations. 8 This contrasted with the ERG status of HGPIN.…”
Section: Discussionsupporting
confidence: 90%
“…IDC-P, for instance, has been suggested as a defined morphological entity that is associated with worse prognosis [4850]. More recent cytogenetic and IHC studies suggested a clonal relationship with adjacent invasive prostate cancer based on ERG [42,59]. In the present study, a subset of cases for which clonality was addressed using TMPRSS2–ERG breakpoint analysis contained IDC-P.…”
Section: Discussionmentioning
confidence: 64%
“…This is because diagnostic usefulness of ERG has been revealed in prostate pathology especially dealing with intraductal neoplastic lesion [15]. Expression status of ERG in intraductal carcinoma of the prostate and its adjacent conventional adenocarcinoma was the same; it is thus supposed that intraductal carcinoma of the prostate is a lesion reflecting colonization of conventional adenocarcinoma in benign glands [16]. Another intraductal lesion, high-grade prostatic intraepithelial neoplasia, was similar to intraductal carcinoma of the prostate in morphology, but was not immunostained with ERG [15].…”
Section: Discussionmentioning
confidence: 94%